2014
DOI: 10.1371/journal.pone.0112706
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Evaluation of Reference Genes for Expression Studies with Quantitative PCR in the Model Fungus Neurospora crassa under Different Environmental Conditions in Continuous Culture

Abstract: Neurospora crassa has served as a model organism for studying circadian pathways and more recently has gained attention in the biofuel industry due to its enhanced capacity for cellulase production. However, in order to optimize N. crassa for biotechnological applications, metabolic pathways during growth under different environmental conditions must be addressed. Reverse-transcription quantitative PCR (RT-qPCR) is a technique that provides a high-throughput platform from which to measure the expression of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The three significant differences between the experimental setup and results generated for this manuscript compared to the results presented by Crosthwaite and coworkers was the use of dynamic agitation to disperse the cellular material through the experiment, a significantly slower dilution rate (60.3 ± 0.7 mL/h vs. 0.074 ± 0.004 mL/h) to maintain steady state, and choice of reference genes ( btl and vma2 ) 32 . The amount of CO 2 generated remained steady between 3500–4000 ppm for both LD and DD experiments and confirmed that a steady metabolic state was maintained during these experiments ( Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The three significant differences between the experimental setup and results generated for this manuscript compared to the results presented by Crosthwaite and coworkers was the use of dynamic agitation to disperse the cellular material through the experiment, a significantly slower dilution rate (60.3 ± 0.7 mL/h vs. 0.074 ± 0.004 mL/h) to maintain steady state, and choice of reference genes ( btl and vma2 ) 32 . The amount of CO 2 generated remained steady between 3500–4000 ppm for both LD and DD experiments and confirmed that a steady metabolic state was maintained during these experiments ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Periodic patterns in frq transcription are considered a reliable indicator of circadian gene oscillations in N. crassa 9 . These patterns were determined by RT-qPCR using stable reference genes for continuous culture conditions ( btl and vma2 ) 32 . The periodicity of this overt rhythm can be entrained by exposing the cultures to light.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…β ‐tubulin was used to normalize N‐acety1‐β‐D‐glucosaminidase gene in C. rosea when confronting with Fusarium culmorum (Mamarabadi, Jensen, & Lübeck, ), however, it was not available in mycoparasitic process (Sun, Li, & Sun, ; Sun, Sun, & Li, ). In Neurospora crassa , the expression of act was not affected by temperature, but it was inhibited under all‐dark conditions (Cusick et al., ). Therefore, selection of suitable reference genes under a specific condition is crucial for accurate gene normalization and function certification.…”
Section: Introductionmentioning
confidence: 99%